Development of Space Weather Reasonable Worst‐Case Scenarios for the UK National Risk Assessment. Issue 4 (8th April 2021) - Hapgood, Mike; Angling, Matthew J.; Attrill, Gemma; Bisi, Mario; Cannon, Paul S.; Dyer, Clive; Eastwood, Jonathan P.; Elvidge, Sean; Gibbs, Mark; Harrison, Richard A.; Hord, Colin; Horne, Richard B.; et al.
Abstract: Severe space weather was identified as a risk to the UK in 2010 as part of a wider review of natural hazards triggered by the societal disruption caused by the eruption of the Eyjafjallajökull volcano in April of that year. To support further risk assessment by government officials, and at their request, we developed a set of reasonable worst‐case scenarios and first published them as a technical report in 2012 (current version published in 2020). Each scenario focused on a space weather environment that could disrupt a particular national infrastructure such as electric power or satellites, thus, enabling officials to explore the resilience of that infrastructure against severe space weather through discussions with relevant experts from other parts of government and with the operators of that infrastructure. This approach also encouraged us to focus on the environmental features that are key to generating adverse impacts. In this paper, we outline the scientific evidence that we have used to develop these scenarios, and the refinements made to them as new evidence emerged. We show how these scenarios are also considered as an ensemble so that government officials can prepare for a severe space weather event, during which many or all of the different scenarios will materialize. Finally, we note that this ensemble also needs to include insights into how public behavior will play out during a severe space weather event and hence the importance of providing robust, evidence‐based information on space weather and its adverse impacts. Plain Language Summary: Severe space weather was identified as a risk to the UK in 2010 as part of a wider review of natural hazards following the societal disruption that arose when airspace was closed in April 2010 due to volcanic ash. To support further risk assessment by government officials, we developed a set of scenarios, each focused on how severe space weather conditions could disrupt a particular national infrastructure, e.g. the impact of large rapid geomagnetic field changes on the power grid. These scenarios enabled officials to discuss infrastructure resilience against space weather with relevant experts in government and industry. In this paper, we outline the scientific evidence that we have used to develop these scenarios, and the refinements made to them as new evidence emerged. We also show how these scenarios may occur close together in time so that government officials must prepare for the near‐simultaneous occurrence of many different problems during a severe space weather event, including the need to consider how public behavior will play out during a severe space weather event. This highlights the importance of providing robust, evidence‐based information on space weather and its adverse impacts. Key Points: Reasonable worst‐case scenarios have been developed to support assessment of severe space weather within the UK National Risk Assessment Individual scenarios focus on space weather features that disrupt a particular national infrastructure, e.g. electric power or satellites Treat these scenarios as an ensemble, enabling planning for a severe space weather event within which many of these features will arise